Environmental and Social responsibility as a corporate strategy in small businesses mechanical metal industry - Monaro, Daniel Luis Garrido; Plens, Ana Carolina de Oliveira; Monaro, Renato Luis Garrido; Assumpção, Maria Rita Pontes; Coutinho, Aparecido dos Reis (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The integration between processes and sustainability, also known as the Triple Bottom Line (TBL), contributes to structure of an organization in terms of competitiveness, so that changes in favor of the environment starts to benefit the corporation relation sustainability and society at the strategic level decision making in a corporation. This work aims to identify and assess the practical application of Corporate Social Responsibility and its interaction with the environment through the identification of environmental responsibility as a competitive strategy. Thus, it was develop a case study on three companies in the metal mechanic sector through the application of questionnaire adapted from ETHOS Institute, to evaluate their practices aimed at sustainability, “green” practice and the level of commitment of the same with preserving the environment and society to its surroundings. Thus, Company A showed little actions in favor of environmental and social guidelines, while Company B presented initiatives for the social aspects and the Company C showed better results in relation to environmental requirements, which showed different business strategies to search for a gap in the market.